I am me: using buoyant biopsychosocial art education curriculum and storyboards to explore self-esteem with sixth grade students - Harlow, Trina D. (Kansas State University, 2019)
Schools must adapt to the needs of the 21st century learner. Relevant, meaningful curriculum with important implications toward students’ needs and cultures through their biographies, psychologies, and sociologies brings value to the learner, school, and society. This instrumental, single case study sought to explore how a specific curriculum developed for this study–I Am Me: THOUGHTS of Buoyancy–could teach an understanding of self-esteem to sixth-graders that would then be potentially exhibited in art making and reflection. While the curriculum unit developed for this study had six art projects and eight lesson plans, the I Am Me Storyboard art project was the central focus of data analysis. Buoyancy was used as a metaphor to assist in teaching the meaning of self-esteem. Instrumental case study was implemented by the examination of the case for larger implications in 21st century art education. By investigating the development of an intercultural classroom through art activities and art making and by using the art curriculum for social emotional learning, the curriculum was analyzed for its usefulness in providing meaningful learning above and beyond art content within middle school art classes. Arts Based Research (Leavy, 2018) was the theoretical framework for the study, building on the work of Eisner (2002) and Dewey (1934). The study was a meta-synthesis of art education curriculum, storytelling, and biopsychosocial education with a pedagogical focus on Culturally Responsive Teaching (Gay, 2018) and Biography Driven Instruction (Herrera, 2016). This study built upon the research of early adolescent self-esteem by DuBois, Felner, Brand, Phillips, and Lease (1996), which categorized evidence of self-esteem into the five categories of family, friends, activities, body image, and school. The acronym “EASEA” was developed during this study to represent Early Adolescent Self-esteem Analysis, encompassing these five categories of self-esteem. The intent of the student artists–the participants–was analyzed using visual, verbal, and “vervisual” examination. The term vervisual was developed for this study to represent a third zone of communication in which visual and verbal communication are used in tandem to inform meaning. A variety of data sources were used including field notes, interviews, information provided by students’ parents or guardians, and five different artistic phases of the storyboard that included the art making and a written or verbal artist statement for each phase. Findings of the study revealed that students told recognizable visual and verbal stories depicting components of self-esteem in a variety of ways. Students told stories in implicit or explicit ways that sometimes needed both the visual artifact and the verbal statement to be fully understood. Students felt empowered by having control over how much of their story they chose to tell. Through their art making and written or verbal artist statements, many students chose to share joyous aspects of their lives reflecting things they loved, that brought them laughter, or that represented their lives (Herrera, 2016). Students shared biopsychosocial aspects of their lives and their social emotional needs were addressed through the planned curriculum or given an opportunity to be explored. By choice, some students shared difficult aspects of their personal lives. Data revealed that all ten trauma reflecting communications were first completed as drawings in the geometric design phase where students drew a symbol representing their past, present, and future. Findings revealed that after students first drew an image, they then felt freer to write a written description of what they had drawn. Another unique finding of the study was that the various components of students’ storyboards depicted a visual rhythm or movement that cohesively and aesthetically conveyed a vervisual language, unique to each student. The study was also particularly revealing with newcomer (refugee) students and recent immigrants, giving them a platform to share their experiences prior to going to school in the United States and expressing the importance of their culture. The findings indicate that curriculum such as I Am Me: THOUGHTS of Buoyancy has a place in art education, that university pre-service art education programs should investigate the inclusion of social emotional learning courses for students majoring in art education, and that art educators should work with school counselors in developing art curriculum that addresses character traits and other issues of concern with middle school students.
Keywords: Art education; Arts based research; Biography driven instruction; Biopsychosocial; Self-esteem; Storytelling